2017
DOI: 10.1038/ajg.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Early Aggressive Hydration Hastens Clinical Improvement in Mild Acute Pancreatitis

Abstract: Early aggressive intravenous hydration with Lactated Ringer's solution hastens clinical improvement in patients with mild acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 22 publications
1
97
1
9
Order By: Relevance
“…One RCT in 60 patients with predicted mild pancreatitis demonstrated that aggressive fluid hydration with Ringer’s lactate (20 mL/kg bolus followed by 3 mL/kg/h) compared with standard hydration with Ringer’s lactate (10 mL/kg bolus followed by 1.5 mL/kg/h) improved a composite end point (ie, ‘clinical improvement within 36 hours’) 19. So, both too little as well as too much fluid administration in the acute phase of pancreatitis can be harmful, possibly dependent on the severity of the pancreatitis.…”
Section: Early Phase Of Acute Pancreatitismentioning
confidence: 99%
“…One RCT in 60 patients with predicted mild pancreatitis demonstrated that aggressive fluid hydration with Ringer’s lactate (20 mL/kg bolus followed by 3 mL/kg/h) compared with standard hydration with Ringer’s lactate (10 mL/kg bolus followed by 1.5 mL/kg/h) improved a composite end point (ie, ‘clinical improvement within 36 hours’) 19. So, both too little as well as too much fluid administration in the acute phase of pancreatitis can be harmful, possibly dependent on the severity of the pancreatitis.…”
Section: Early Phase Of Acute Pancreatitismentioning
confidence: 99%
“…From multiple adult studies it can be concluded that aggressive resuscitation is associated with improved outcomes in AP, but overresuscitation should be avoided. A regimen of IV fluids within 4 hours of diagnosis to aggressive (20 ml/kg bolus followed by 3 ml/kg/h) vs. standard (10 ml/kg bolus followed by 1.5 mg/kg/h) hydration with lactated Ringer's solution was associated with greater rate of clinical improvement 75 .…”
mentioning
confidence: 93%
“…Unfortunately, diversity of inclusion criterion makes it challenging to identify which groups of patients benefit from specific therapy. Additionally, while objective acute pancreatitis outcomes such as death are fortunately rare this necessitates the use of surrogate measures such as clinical improvement or changes in cytokine levels as study endpoints [1, 5]. The use of scoring systems that predict severity of disease have predominated in the acute pancreatitis field.…”
Section: Introductionmentioning
confidence: 99%